2015
DOI: 10.1378/chest.15-0164
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Intervention Fidelity and Recommendations for Researchers Conducting Studies on the Diagnosis and Treatment of Chronic Cough in the Adult

Abstract: Only low-quality evidence supports that intervention fidelity strategies were used when conducting primary research in diagnosing and managing chronic cough in adults. This supports the contention that some of the variability in the reporting of patients with unexplained or unresolved chronic cough may be due to lack of intervention fidelity. By following the recommendations and suggestions in this article, researchers will likely be better able to incorporate strategies to address intervention fidelity, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 40 publications
(40 reference statements)
0
35
0
Order By: Relevance
“…These processes are detailed in the CHEST chronic cough guideline, 2 as well as in other cough reviews. 4,5 The completeness of this assessment and treatment approach according to the five areas of intervention fidelity (study design, training of providers, delivery of treatment, receipt, and enactment of treatment) 41 is recognized as an important paradigm in the determination of UCC. Although the studies reviewed in this assessment showed fair to good adherence to intervention fidelity, there are clearly opportunities to provide better documentation of the assessment process in published reports.…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…These processes are detailed in the CHEST chronic cough guideline, 2 as well as in other cough reviews. 4,5 The completeness of this assessment and treatment approach according to the five areas of intervention fidelity (study design, training of providers, delivery of treatment, receipt, and enactment of treatment) 41 is recognized as an important paradigm in the determination of UCC. Although the studies reviewed in this assessment showed fair to good adherence to intervention fidelity, there are clearly opportunities to provide better documentation of the assessment process in published reports.…”
Section: Diagnosismentioning
confidence: 99%
“…There is also a need to consistently use validated outcome assessment tools when evaluating treatment response in chronic cough. Current CHEST guidelines directed at strengthening future studies of cough provide recommendations for incorporating the use of an intervention manual and other intervention fidelity strategies in chronic cough studies 41 and also detail validated tools developed for assessing cough outcomes. 42 The use of an intervention fidelity tool will facilitate the strengthening of study quality in chronic cough research.…”
Section: Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…A guideline based chronic cough assessment is an essential part of the investigation of these patients. 64 66 Once this has been completed and the results reviewed, if the cough persists then the patient can be diagnosed as having chronic refractory cough.…”
Section: Diagnosis Of Chronic Refractory Cough Primary Assessmentmentioning
confidence: 99%
“…Thus, COPD can be para-, meta-, and post-tuberculosis process [1]- [4]. Both diseases have similar risk factors: smoking, low socio-economic status of the individual and the violation of the immune defense [5]- [7]. A related aspect of the above pathogenetic nosology is the development of destructive changes in the pulmonary parenchyma, caused, in particular, a metabolic disorder due to exposure to tobacco metalloproteinases or virulence factors Mycobacterium tuberculosis [2] [5] [8].…”
Section: Purposementioning
confidence: 99%